Praktik Pengelolaan Arus Kas dalam Usaha Mikro: Perspektif Pengusaha UMKM Wanita - Ita Athia; Sudarmiatin Sudarmiatin2; Agus Hermawan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study explores the cash management practices of women-owned Small and Medium Enterprises (SMEs) in Indonesia. Through qualitative research using the ethnographic method, including observations and interviews with three female entrepreneurs in Batu and Malang, East Java, the study reveals insights into their practices. The findings show varying understandings of cash flow management among female entrepreneurs. Cash flow planning is done by estimating monthly income and expenses, setting sales targets, and creating monthly financial reports. Entrepreneurs have different perspectives on business development and expansion. Some plan to expand their businesses, while others focus on stable growth. Debt is seen as a burden if not managed well but can be beneficial for business development. Entrepreneurs also prioritize savings for emergencies and business needs. These findings contribute to understanding the cash management practices of women-owned SMEs in Indonesia. The study emphasizes the importance of financial literacy and provides insights into cash flow management practices that can enhance business operations.